2020
DOI: 10.1177/2397847320972040
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin abates reproductive toxicity mediated by the oxido-inflammatory response in Doxorubicin-treated rats

Abstract: The anti-neoplastic use of Doxorubicin (DOX) is hampered by several limitations, including reproductive toxicity. Luteolin (LUT)–a phytochemical-biological benefits include antioxidative and anti-inflammatory actions. Here we examined the protective effect of LUT against DOX-induced reproductive toxicity in an in vivo model—male albino Wistar rats—randomly assigned to five groups and treated as follows: Control (corn oil 2 mL/kg; per os), LUT (100 mg/kg; per os), DOX (2 mg/kg) by intraperitoneal injections, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 93 publications
(115 reference statements)
2
10
0
Order By: Relevance
“…A significant perturbation in the dynamic processes of spermatogenesis is evidenced by decreased sperm functional parameters of epididymal sperm count, viability, and motility, and increased sperm abnormalities manifested in the head, tail, and midpiece of sperm. This observation agrees with previous findings in our laboratory and other laboratories (Owumi, Ijadele, et al, 2020;Sharma et al, 2020) that sperm parameters evaluated in this study were negatively affected by AFB 1 . Interestingly, CA abrogated AFB1-induced reproductive toxicity by increasing the indices of sperm functionality and decreasing the index of sperm abnormalities in the experimental animals.…”
Section: Discussionsupporting
confidence: 94%
“…A significant perturbation in the dynamic processes of spermatogenesis is evidenced by decreased sperm functional parameters of epididymal sperm count, viability, and motility, and increased sperm abnormalities manifested in the head, tail, and midpiece of sperm. This observation agrees with previous findings in our laboratory and other laboratories (Owumi, Ijadele, et al, 2020;Sharma et al, 2020) that sperm parameters evaluated in this study were negatively affected by AFB 1 . Interestingly, CA abrogated AFB1-induced reproductive toxicity by increasing the indices of sperm functionality and decreasing the index of sperm abnormalities in the experimental animals.…”
Section: Discussionsupporting
confidence: 94%
“…Based on our findings, we conclude that the protective effect of LUT against DOX-induced neurotoxicity is via a combination of LUT scavenging ability of ROS/RNS, inhibition of proapoptotic proteins and markers of inflammations as earlier observed in our previous studies on other target organs. [31,54,55] Our previous findings are indicative of LUT readily bioavailability that can therefore confer protection against oxidative damage in various organs. cerebrum and hypothalamus weight (Table 1), similar to another study.…”
Section: Discussionmentioning
confidence: 66%
“…[74] LUT coadministration, improved In conclusion, previous studies have demonstrated that LUT could ameliorate systemic toxicities caused by DOX-based chemotherapy. [18,31,[72][73][74] The BBB penetrability of LUT, together with its neuroprotective and anti-inflammatory effects, makes it an ideal small molecule to investigate the prospect of its ability to protect against or reverse DOX-induced cognitive dysfunction, a serious side-effect that has not garnered much attention as the wellestablished cardiotoxic effects of DOX. We presently demonstrate that DOX treatment can result in toxic outcomes in a male rat's brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid peroxidation was determined by quantifying thiobarbituric acid reactive substances (TBARS) in the testicular and epididymal homogenates using the previously reported method of Buege and Aust (Buege & Aust, 1978;Owumi, Ijadele, et al, 2020). Test samples (40 µl) was mixed with 0.15 M Tris-KCl buffer (160 µl; pH: 7.4) containing 30% TCA (50 µl).…”
Section: Determination Of Lipid Peroxidation Levelmentioning
confidence: 99%